Helicobacter pylori-Induced IL-1β secretion in innate immune cells is regulated by the NLRP3 inflammasome and requires the cag pathogenicity Island - Semper, Raphaela P.; Mejías-Luque, Raquel; Groß, Christina; Anderl, Florian; Müller, Anne; Vieth, Michael; Busch, Dirk H.; Da Costa, Clarissa Prazeres; Ruland, Jürgen; Groß, Olaf; Gerhard, Markus (Journal of Immunology, 2014)
Infection with the gram-negative bacterium Helicobacter pylori is the most prevalent chronic bacterial infection, affecting 50% of the world's population, and is the main risk factor of gastric cancer. The proinflammatory cytokine IL-1β plays a crucial role in the development of gastric tumors and polymorphisms in the IL-1 gene cluster leading to increased IL-1β production have been associated with increased risk for gastric cancer. To be active, pro-IL-1β must be cleaved by the inflammasome, an intracellular multiprotein complex implicated in physiological and pathological inflammation. Recently, H. pylori was postulated to activate the inflammasome in murine bone marröwCderived dendritic cells; however, the molecular mechanisms as well as the bacterial virulence factor acting as signal 2 activating the inflammasome remain elusive. In this study, we analyzed the inflammasome complex regulating IL-1β upon H. pylori infection as well as the molecular mechanisms involved. Our results indicate that H. pylori-induced IL-1β secretion is mediated by activation of the nucleotide-binding oligomerization domain-like receptor family, pyrin domain-containing 3 inflammasome. We also show that reactive oxygen species, potassium efflux, and lysosomal destabilization are the main cellular mechanisms responsible of nucleotide-binding oligomerization domain family, pyrin domaïnCcontaining 3 inflammasome activation upon H. pylori infection, and identify vacuolating cytotoxin A and cag pathogenicity island as the bacterial virulence determinants involved. Moreover, in vivo experiments indicate an important role for the inflammasome in the onset and establishment of H. pylori infection and in the subsequent inflammatory response of the host.
CRIS-Team Scopus Importer:2025-03-05